Habitat amount versus connectivity: An empirical study of bird responses. (January 2020) - Lindenmayer, David B.; Blanchard, Wade; Foster, Claire N.; Scheele, Ben C.; Westgate, Martin J.; Stein, John; Crane, Mason; Florance, Dan
Abstract: Habitat loss is widely acknowledged as a key driver of global biodiversity decline. However, whether biodiversity loss occurs in response to reductions in habitat amount versus reductions in connectivity in fragmented landscapes is debated. A challenge in resolving this issue is that measures of the amount of native woody vegetation cover and those calculated for structural connectivity are often highly correlated. Using multi-season detection-occupancy models we address the question: After accounting for the effects of native woody vegetation cover, what is the contribution of structural connectivity to site occupancy, site persistence and site colonization by birds? In this context, structural connectivity corresponded to the configuration of vegetation cover in the landscape surrounding our sites. We constructed multi-season detection-occupancy models for 44 individual bird species based on long-term field surveys in the temperate woodlands of eastern Australia. We found responses to vegetation amount were far more prevalent than responses to structural connectivity (35 vs 6 species). The range of responses by different species to vegetation amount, to structural connectivity, or to both, suggests that these elements have different effects on the processes of occupancy, persistence and colonization. The predominance of vegetation amount effects in our study, particularly the positive effects for a range of species of conservation concern, suggests the critical importance of both conserving existing areas of native vegetation cover and increasing the amount of that cover. At least for birds, efforts to physically connect particular patches may have relatively less benefit compared to programs to boost overall vegetation cover. Highlights: Biodiversity loss can result from changes in habitat loss and connectivity. We tested their relative effect on birds in a 13 year study. Habitat amount was a more prevalent variable in occupancy models than connectivity. Responses to total vegetation cover and to connectivity were not always positive. Land managers should identify species targeted by vegetation restoration actions.